Lactulose in combination with soybean lecithin has a cryoprotective effect on probiotic taxa of bifidobacteria and Lactobacillaceae - Killer, Jiří; Bunešová, Věra Neužil; Modráčková, Nikol; Vlková, Eva; Pechar, Radko; Šplíchal, Igor (Letters in applied microbiology, 2023)
Lactulose is commonly used in pharmacy for constipation and hepatic encephalopathy treatment. The prebiotic effect of lactulose is also often mentioned. However, its cryoprotective effect in combination with lecithin on the main representatives of probiotics has not been tested yet. The 12 taxa of bifidobacteria and Lactobacillaceae members were used for the purpose. These were mixed in a ratio of 1:1 with lactulose + lecithin (finally 5.0% and 1.25%, respectively; LL). The 25% glycerol (G+) solution and cultures themselves were applied as positive and negative controls, respectively. Bacterial suspensions were stored at a mild freezing temperature (-20°C) until the end of the experiment (210th day). The LL solution had a comparable (insignificant difference at the P-value = 0.05) cryoprotective effect as the positive control in five of six bifidobacteria and in three of six representatives of Lactobacillaceae. The better cryoprotective effect was revealed in other Lactobacillaceae. At the end of the experiment, the generally accepted therapeutic minimum (>107 Colony Forming Units/mL) was determined in LL solution in five bifidobacteria and four Lactobacillaceae strains. The presented results improve knowledge about long-term mild cryopreservation of the most commonly used probiotics and could contribute to developing new forms of (nutri)synbiotics.
Keywords: Cryoprotective Agents; probiotika; kryoprotektivní látky; Glycine max; Bifidobacterium; Lecithins; lecitiny; Probiotics; Lactulose; laktulosa; Lactobacillaceae